Transperineal ultrasound evaluation of females with stress urinary incontinence - Sweed, Mohamed S.; Sharara, Sherene (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Urinary incontinence has a significant influence on the well-being of affected females. No standard imaging modality is mandatory in initial evaluation of patients with urinary incontinence. Transperineal ultrasound has been proposed as a reliable method to assess female stress urinary incontinence. This study was conducted to evaluate the transperineal ultrasound findings in females with stress urinary incontinence. Methods: A case-control study including 40 females diagnosed to have stress urinary incontinence and 40 healthy females as their controls. The proximal pubo-urethral distance, the posterior urethro-vesical angle (β-angle) and the angle of urethral inclination (α-angle) were measured at rest and during straining. Results: On analyzing the transperineal ultrasound findings, no statistical significant difference was found between cases and controls at rest, but on straining, statistical significant difference was found regarding dynamic posterior urethral angle and dynamic pubo-urethral distance (p <0.001). Of the included 40 cases with SUI, 27 (67.5%) had cysto-urethrocele, and 5 (12.5%) had intrinsic sphincter defect (ISD). Urethral diameter was significantly different in patients with ISD (6.64±1.23 mm) when compared with patients with SUI without ISD (4.83±1.16 mm). Conclusions: Transperineal ultrasound is a simple, noninvasive, and easily conducted examination that can be used in the diagnostic workup of stress incontinence.